Evaluation of Complex Formation during polymerization of Acrylamide Initiated by Ce(IV) Aminopolycarboxylate Ligands - Nalla Mohamed, K.E.N. (Asian Journal of Chemistry, 2010)
The aqueous polymerisation of acrylamide initiated by Ce(IV)aminopolycarboxylate ligands (APCL) like glycine (GLY), iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), 1,2-diaminocyclohexanetetraacetic acid (CDTA), ethylenediaminetetraacetic acid (EDTA), and diethylenetriamine pentaacetic acid (DTPA) are investigated. These APC ligands form stable complexes with Ce(IV). In the presence of monomer acrylamide these complexes get decomposed to form ligand radicals (R) which initiated the polymerisation reaction. Such a type of system is characterised by the formation constant 'K' and decomposition (disproportionation) constant kd. K and kd values are evaluated for the above six systems, by determining the rate of disappearance of Ce(IV) in the polymerisation experiment in which the concentration of the ligand is varied keeping [Ce(IV)] as constant. The complex formation is supported by the absorption spectra.